Modul Pembelajaran Berbasis Saintifik Dengan Metode IOC (Inside Outside Circle) Pada Pelajaran IPS Kelas V SD/MI - Asmahasanah, Salati; Sari, Ratna; Supriatna, Irfan (UNIB Press, 2021)
The purpose of this study was to determine the feasibility and process of developing a scientific-based social studies learning module using the IOC (Inside Outside Circle) method for grade 5 SD / MI. The method used in this research is Sugiyono's Research and Development (R&D) method. Sugiyono's Research and Development (R & D) method has 10 stages but in this research it is only limited to the expert / expert validation stage this is due to the Covid-19 pandemic which has made the face-to-face learning process in schools shifted to online learning this raises several problems in the process research so that it does not allow researchers to test products to students. Data collection was carried out through the learning module validation process. The learning module is validated by 3 experts / experts, namely: linguists, design experts and material experts. The results of the validation trial show that the science-based social studies learning module with the IOC (Inside Outside Circle) method is valid. It is said to be valid because the science-based social studies learning module with the IOC (Inside Outside Circle) method developed has met the validity criteria with the